Efforts to Improve Student Learning Activities Using the Quantum Learning Model Theme of Events in Life Class V SD 101911 Sidodadi Batu 8 Pagar Merbau - Putri, Sartika Eka; Landong, Ahmad (Widyagogik, 2023)
This study aims to: (1) determine the results of student learning activities before learning by using the Quantum Learning model on the theme of life events in class V SD Negeri 101911 Sidodadi Batu 8 Deli Serdang. (2) knowing the efforts to increase student learning activities using the Quantum Learning model on the theme of events in life in class V SD Negeri 101911 Sidodadi Batu 8 Deli Serdang. Based on the results of observations and tests filled out by students, it can be concluded that teachers have been able to maintain and improve the implementation of teaching and learning activities using the Quantum Learning model and learning video media. This is based on the results of observations which show an increase with the improvement of teaching and learning activities based on observer observations. Student learning activities have also increased, this can be seen from the increase in the average percentage of student learning activities, namely in cycle I 68% to 91% in cycle II. It can be concluded that the percentage of student learning activities using the Quantum Learning model and learning video media in cycle II has increased by 41%. The percentage of implementation of the Quantum Learning model using video reaches 89% in teacher (researcher) activities in carrying out learning in the classroom.